2023
DOI: 10.1186/s40359-023-01247-7
|View full text |Cite
|
Sign up to set email alerts
|

Work addiction in Chinese white-collar workers: the psychometric properties of its measure and its comorbidity with general anxiety in network analysis

Abstract: Background Work addiction (WA) threatens occupation-related health in many countries including China. This research aims to evaluate the psychometric properties of the Chinese version of Bergen Work Addiction Scale (BWAS), the most common measure of WA, to facilitate relevant studies in Chinese workers. A network analysis was further conducted to identify central and bridge symptoms within the WA-anxiety network to improve intervention practices. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 84 publications
1
7
0
Order By: Relevance
“…Taking into account feedback loops, it can be expected that increasing problems may increase mood modification needs and aggravate tolerance, withdrawal, and relapse symptoms. These assumptions seem to find support in previous research (Atroszko et al, 2017; Bellali et al, 2023; Denizci Nazlıgül et al, 2022; Falco et al, 2022; Fekih-Romdhane et al, 2022; Molino et al, 2022; Sun et al, 2023). Therefore, we argue that work addiction could be conceptualized as a network of direct relationships between its symptoms.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…Taking into account feedback loops, it can be expected that increasing problems may increase mood modification needs and aggravate tolerance, withdrawal, and relapse symptoms. These assumptions seem to find support in previous research (Atroszko et al, 2017; Bellali et al, 2023; Denizci Nazlıgül et al, 2022; Falco et al, 2022; Fekih-Romdhane et al, 2022; Molino et al, 2022; Sun et al, 2023). Therefore, we argue that work addiction could be conceptualized as a network of direct relationships between its symptoms.…”
Section: Introductionsupporting
confidence: 78%
“…In light of previous research, it is important to point out that eight of the strongest edges in this study overlap with two out of the five strongest edges observed by Sun et al (2023), and five out of seven correlations between residuals in previous research grounded in the latent variable framework (two of them overlapping with Sun et al, 2023; see Table 1). These results seem to indicate that both previous network studies and latent variable studies may constitute a valid source of hypotheses for future network studies of work addiction.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations